HUBUNGAN KEPADATAN HUNIAN DAN PENGETAHU A N DENGAN PERILAKU HIDUP BERSIH DAN SEHAT - Su, Hansen Maikel (Politeknik Kesehatan Kemenkes Sorong, 2022)
PHBS indicators are still low and need a health strategy, namely not smoking at home (46.3%), offering exclusive breastfeeding (31.6%), washing hands using soap and clean water (27.2%), doing physical activity every day. day (25.8%), and consume fruits and vegetables every day (0.8%). The purpose of this study was to determine the density of occupancy and knowledge about clean living behavior and at the Makbon Public Health Center. This research is aquantitative research using a cross-sectional approach. The study involved 46 respondents who had problems with PHBS. Sampling was taken using a total sampling technique. The test used was Spearman's rho at a confidence level (α) of 0.05. The results of statistical tests, there is no relationship between residential density and clean and healthy living behavior with the value of the Spearman's rho test value of p = 0.914 > = 0.05 and there is a relationship between knowledge and clean and healthy living behavior with the value of Spearman's rho value = 0.002 < = 0.05 at the Makbon Health Center. In conclusion, there is no relationship between advertising with clean and healthy living behavior and there is a relationship with clean and healthy living behavior.